Properties of concrete with partial rice husk as fine aggregate replacement - Isma Farhan, Roslan (2017)
This study aimed to determine properties of concrete with rice husk as partial replacement of fine aggregate or sand and to evaluate optimum ratio of rice husk in modified concrete. This study establishes the limit to determine the properties of rice husk ratio with ratio of 5 %, 10% and 15% from the basic concrete grade C25/30. There are 36 beams are provided with different ratio of replacement of sand with Rice Husk concrete in this study. The dimension size of beam is 150 mm of width, 150 mm of height and 750 mm of length. There are 36 cubes which dimension size of 150 mm width, 150 mm height and 150 mm length are provided to obtain the average results of the compressive strength. This study also aims to help contribute to the industry in saving the environment, to encourage the government to find solutions regarding the disposal to landfills of waste materials and save the environment, to provide new knowledge to the contractors and developers on how to improve the construction industry methods and services by using rice husk and to sustain good product performance and meet recycling goals. Observations from the tests performed were conducted in the laboratory where precise data were gathered and completely attained.